Nadharia za uhakiki wa fasihi - Wafula, Richard M.; Njogu, Kimani (Nairobi : Jomo Kenyatta Foundation, 2007)
Theory of literary criticism.
Includes bibliographical references (p. 126-132).
In Swahili.
Keywords: Criticism